Beyond Religiosity: Unpacking the Drivers of Cash Waqf Decisions in Indonesia - Ahmad Agus Hidayat; Andriani Samsuri; Mustofa Mustofa; Nurhayati Nurhayati; Muhammad Rizki Ashari (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This study investigates the determinants of cash waqf decisions among Muslim donors (wakif) in Surabaya, Indonesia, by examining the roles of waqf literacy, income, institutional trust, and altruistic attitudes. Furthermore, it assesses whether religiosity strengthens the relationship between these factors and cash waqf decisions. Method: A quantitative research design was employed using a survey of 350 cash waqf donors in Surabaya. Data were analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) to evaluate both direct and moderating effects among the proposed variables. Result: The findings reveal that waqf literacy and institutional trust have a positive and significant influence on cash waqf decisions. In contrast, income and altruistic attitudes do not significantly affect the decision to participate in cash waqf. The results also indicate that religiosity does not moderate the relationships between waqf literacy, income, institutional trust, altruistic attitudes, and cash waqf decisions. Implication: The study highlights the importance of strengthening waqf literacy programs and improving institutional professionalism, transparency, and accountability to enhance public participation in cash waqf. Waqf institutions should prioritise trust-building mechanisms rather than relying solely on religious appeals in fundraising strategies. Originality or Novelty: This study extends the application of the Theory of Planned Behaviour (TPB) to Islamic social finance by examining actual cash waqf decisions rather than behavioural intentions. It also contributes to the literature by testing religiosity as a moderating variable and providing empirical evidence from Surabaya, a newly designated waqf city in Indonesia.